contestada

the following statement is true about the system equation given below x - 2y equals -6 + 4x + y equals 21

Respuesta :

Answer:

x = 25/3    y = -19/3

Step-by-step explanation:

First, solve for one of the variables:

-6 + 4x + y = 21  -->  4x + y = 27  -->  y = -4x + 27

Then plug in y into the original equation to obtain x

x - 2(-4x + 27) = 21 --> x + 8x - 54 = 21  -->  9x = 75  -->  x = 25/3

Then plug this x value in the original equation to obtain y

(25/3) - 2y = -6 + 4(25/3) + y   -->  25/3 - 2y = -6 + 100/3 + y   -->   25/3 - 2y = 82/3 + y   -->  -3y = 57/3  -->  -3y = 19   -->  y = -19/3